Cerebral cavernous malformations form an anticoagulant vascular domain in humans and mice - Lopez-Ramirez, Miguel Alejandro; Pham, Angela; Girard, Romuald; Wyseure, Tine; Hale, Preston; Yamashita, Atsuki; Koskimäki, Janne; Polster, Sean; Saadat, Laleh; Romero, Ignacio A; Esmon, Charles T; Lagarrigue, Frederic; et al. (Blood, 2019)
Cerebral cavernous malformations (CCMs) are common brain vascular dysplasias that are prone to acute and chronic hemorrhage with significant clinical sequelae. The pathogenesis of recurrent bleeding in CCM is incompletely understood. Here, we show that central nervous system hemorrhage in CCMs is associated with locally elevated expression of the anticoagulant endothelial receptors thrombomodulin (TM) and endothelial protein C receptor (EPCR). TM levels are increased in human CCM lesions, as well as in the plasma of patients with CCMs. In mice, endothelial-specific genetic inactivation of ( ) or ( ), which cause CCM formation, results in increased levels of vascular TM and EPCR, as well as in enhanced generation of activated protein C (APC) on endothelial cells. Increased TM expression is due to upregulation of transcription factors KLF2 and KLF4 consequent to the loss of or Increased TM expression contributes to CCM hemorrhage, because genetic inactivation of 1 or 2 copies of the gene decreases brain hemorrhage in mice. Moreover, administration of blocking antibodies against TM and EPCR significantly reduced CCM hemorrhage in mice. Thus, a local increase in the endothelial cofactors that generate anticoagulant APC can contribute to bleeding in CCMs, and plasma soluble TM may represent a biomarker for hemorrhagic risk in CCMs.